The Community In-reach Rehabilitation and Care Transition (CIRACT) clinical and cost-effectiveness randomisation controlled trial in older people admitted to hospital as an acute medical emergency - Sahota, Opinder; Pulikottil-Jacob, Ruth; Marshall, Fiona; Montgomery, Alan; Tan, Wei; Sach, Tracey; Logan, Pip; Kendrick, Denise; Watson, Alison; Walker, Maria; Waring, Justin (Oxford University Press, 2016)
Objective: To compare the clinical and cost-effectiveness of a Community In-reach Rehabilitation and Care Transition (CIRACT) service with the traditional hospital-based rehabilitation (THB-Rehab) service.